Proceedings of the 37th IEEE Conference on Decision and Control (Cat. No.98CH36171)
DOI: 10.1109/cdc.1998.758639
|View full text |Cite
|
Sign up to set email alerts
|

Model reduction, centering, and the Karhunen-Loeve expansion

Abstract: We propose a new computationally efficient modeling method that captures existing translation symmetry in a system. To obtain a low order approximate system of ODEs prior to performing Karhunen Loeve expansion we process the available data set using a "centering" procedure. This approach has been shown to be efficient in nonlinear scalar wave equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Applications of POD include image processing [22], data compression, signal analysis [2], modeling and control of chemical reaction systems [12,25,26], turbulence models [14], coherent structures in fluids [14], control of fluids [10], electrical power grids [21,20,18], and wind engineering to name a few.…”
Section: Background On Proper Orthogonal Decompositionmentioning
confidence: 99%
“…Applications of POD include image processing [22], data compression, signal analysis [2], modeling and control of chemical reaction systems [12,25,26], turbulence models [14], coherent structures in fluids [14], control of fluids [10], electrical power grids [21,20,18], and wind engineering to name a few.…”
Section: Background On Proper Orthogonal Decompositionmentioning
confidence: 99%
“…Experience has shown that if a system has symmetry, then using travelling Karhunen-Loève bases can dramatically cut down the dimension of the reduced system; see, for example, [8,36] and references therein. It is likewise well understood that discrete symmetries are also important to take into account when building bases.…”
Section: Improvementsmentioning
confidence: 99%
“…For model reduction of dynamical systems POD may be used on data points obtained from system trajectories obtained via experiments, numerical simulations, or analytical derivations. For more information see Rathinam and Petzold [13], Holmes, Lumley, and Berkooz [5], Moore [10], Lall, Marsden, and Glavaski [6], Glavaski, Marsden, and Murray [3], and references therein.…”
Section: Podmentioning
confidence: 99%
“…Berkooz [5]), cascading failures in power grids (Parrilo et al [11]), and control of compressors (Glavaski, Marsden, and Murray [3]), etc., and selective modal analysis has been developed by researchers in the electrical power field (Perèz-Arriaga et al [12]), to name a few.…”
mentioning
confidence: 99%